Leadership characters in shadow puppet show - Junaidi, Junaidi (Harmonia: Journal of Arts Research and Education, 2017)
Good leadership characters have been conveyed through the art of puppet. However, in practice, many of us have encountered the opposite fact. This study aims to analyze the leadership characters in the art of puppet. This research is a descriptive qualitative research which uses hermeneutical method to analyze the data gathered from the library research and field study. The data then passes data reduction step, data classification, and data verification. The results show that leadership characteristics in puppet can be formulated into five leadership concepts: (1) dwikridha, (2) tripakarti, (3) caturtama, (4) pancapratama, and (5) hasthabrata. If these five concepts of leadership are known, understood, and done well, our beloved country, Indonesia, will reach welfare together.